Protective effect of Hemidesmus indicus R.Br. root extract against cisplatin-induced cytogenetic damage in mouse bone marrow cells - Ananthi, Rajagopal (Sociedade Brasileira de Genética, 2010)
The aqueous extract of Hemidesmus indicus roots was investigated for its in vivo antigenotoxic effect against cisplatin-induced cytogenetic damage. Swiss albino mice were administered with various doses of the extract either singly (50, 100 and 200 mg/kg body weight) or as split doses (10, 20 and 40 mg/kg bw/day) for five consecutive days by oral gavage. As endpoints, chromosome aberrations, micronuclei in polychromatic erythrocytes, mitotic index and PCE/NCE ratio were estimated. The extract protected the bone marrow cells from cisplatin-induced genotoxicity in an inverse dose-dependent manner. However, the extract was cytotoxic at all doses. But, under split dose regime it conferred a higher level of genoprotection and was not cytotoxic at the lower two doses. The presence of saponins, tannins, phenols, terpenoids, flavonoids and coumarins in the crude extract could explain these effects.